FEASIBILITY OF CORN SILAGE FOR DAIRY CATTLE - Scheler, Eduardo Donizeti; Cavichioli, Fábio Alexandre (Revista Interface Tecnológica, 2021)
Of Mexican origin, the corn was planted by American Indians in heaps, using a complex system that varied the species planted according to its use. Corn silage is now the most used type of silage in Brazil. This is mainly because it manages to provide fodder with lots of energy and protein for cattle, and it is easier to grow than other crops. Corn silage is one of the most important components in the feeding of cattle, since its plant provides a large volume of palatable food, with high digestibility and rich in energy, which results in an excellent potential to produce milk. This article aims to realize the viability of corn silage for dairy cattle through the financial economic analysis through the economic indicators Net present value, Internal rate of return and Payback.